Post-inhaled corticosteroid pulmonary tuberculosis and pneumonia increases lung cancer in patients with COPD. Issue 1 (December 2016) - Wu, Ming-Fang; Jian, Zhi-Hong; Huang, Jing-Yang; Jan, Cheng-Feng; Nfor, Oswald; Jhang, Kai-Ming; Ku, Wen-Yuan; Ho, Chien-Chang; Lung, Chia-Chi; Pan, Hui-Hsien; Wu, Min-Chen; Liaw, Yung-Po
Abstract Background Inhaled corticosteroids (ICS) have been associated with decreased lung cancer risk. However, they have been associated with pulmonary infections (tuberculosis [TB] and pneumonia) in patients with chronic obstructive pulmonary disease (COPD). TB and pneumonia have increased lung cancer risk. The association between post-ICS pulmonary infections and lung cancer remains unclear. Methods We conducted a retrospective cohort study from 2003 to 2010 using the Taiwan National Health Insurance Research Database. Among the 1, 089, 955 patients with COPD, we identified 8813 new users of ICS prescribed for a period of 3 months or more and 35, 252 non-ICS users who were randomly matched for sex, age and date of ICS use from 2003 to 2005. Cox proportional hazard regression was used to estimate the hazard ratio (HR) of pulmonary infections in patients with/without ICS use. Results The HRs for lung cancer in ICS users with sequential lung infections were as follows; 2.42 (95 % confidence interval [CI], 1.28–4.58) for individuals with TB, 2.37 (95 % CI, 1.01–5.54) for TB and pneumonia, and 1.17(95 % CI, 0.69–1.98) for those with pneumonia. For non-ICS users with pulmonary infections, the HRs were 1.68 (95 % CI, 0.78–3.65) for individual with TB and pneumonia, 1.42 (95 % CI, 0.89–2.26) for TB, and 0.95 (95 % CI, 0.62–1.46) for individuals with pneumonia. Conclusions COPD patients with TB /or pneumonia who used ICS had increased risk of lung cancer. Because the overall prognosis of lung cancer remains poor, screening tests are recommended for patients with these conditions.